PERILAKU ETNIS TIONGHOA TERRADAP MOTIF MEMEGANG UANG DI PALEMBANG - Silvia Wati Hidayat; Syaipan Djambak; Suhel Suhel (Department of Development Economics, Universitas Sriwijaya, 2004)
Every person needs money to provide everything they need in life because money is one of the media which can he used legally in exchange. When they keep their money, which are transaction motive, pecunarymotive, and speculative motive. Chinese ethnic is one member of the people in life, and they also do the three motives. But they have their own reason to do their motives in holding differently.This research used qualitative techniques to see how close the relationship between behaviors for The Chinese's motives in holding money and their salary. Salary and fee that received by a person allocated to three motives as every priority which they need, and as a percentage one by one differently. And together with the good support from the banking sectors, the three motives which long time ago do separately, now people do it together. This make every individual very easy· to allocate their money and their salary to anything they want and as they needKeywords: transaction motive, pecunary motive, speculative motive, salary, fee